Campylobacter fetus Bacteremia Revealed by Cellulitis without Gastrointestinal Symptoms in the Context of Acquired Hypogammaglobulinemia: A Report of Three Cases - Souleymane Brah; Laurent Chiche; Marion Brun; Nicolas Schleinitz; Jean-Robert Harle; Jean-Marc Durand (Case Reports in Gastrointestinal Medicine)
Campylobacter fetus bacteremia is rare and occurs mainly in patients with immunosuppression. This infection, which often involves secondary localizations has already been reported in some primary humoral immune deficiencies. We describe three cases of severe infection due to C. fetus with cellulitis at presentation, but without any gastrointestinal symptoms, occurring in patients with acquired hypogammaglobulinemia.